Implementation of Motion Analysis Applications in Watersportsin the Lambung Mangkurat University Environment - Anggara, Norma; Pratiwi, Endang; Sarmidi, Sarmidi (Program Studi Pendidikan Kepelatihan Olahraga Fakultas Ilmu Pendidikan Universitas Bhayangkara Jakarta Raya, 2023)
This study was conducted to determine the ability in water sports. This research is intended to determine motion analysis with the implementation of using the konovea software application. The research is a survey research with descriptive data type. The population in this study were students at Lambung Mangkurat University. The data collection technique used purposive sampling, the sample obtained was 40 people where students who were taking lectures on water sports. Data obtained in the form of video and data analysis using kinovea software. The results showed that swimmers can perform improved movements with an average pass rate of 87% of the results of the evaluation of good and correct movement assessment after analyzing through the use of the application. Then based on the results of thequestionnaire test the level of understanding of the sample as much as 97% has understoodthe use of the kinovea software application.